2021
DOI: 10.1111/ijcp.14606
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 as a potential prognostic biomarker for COVID‐19 disease: Case–control study

Abstract: Background Annexin A1 (AnxA1) is an important endogenous glucocoticoid protein that contributes to the suppression of inflammation by limiting the production of neutrophil and pro‐inflammatory cytokines. This study aims to determine the clinical predictivity value of blood AnxA1 levels in patients with mild and severe–critical pneumonia induced by COVID‐19. Methods This study employed a prospective, case–control study design and was conducted at Ankara Training and Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
(76 reference statements)
0
14
1
Order By: Relevance
“…Annexins are structural proteins that participate in the regulation of inflammatory responses and homeostasis 67 and have been associated with disease severity in COVID-19 (refs. 68 , 69 ). In this circuit, CD14 + and CD16 + monocytes show the potential to receive signals from NK cells and CD8 + T cells for P1D1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexins are structural proteins that participate in the regulation of inflammatory responses and homeostasis 67 and have been associated with disease severity in COVID-19 (refs. 68 , 69 ). In this circuit, CD14 + and CD16 + monocytes show the potential to receive signals from NK cells and CD8 + T cells for P1D1.…”
Section: Resultsmentioning
confidence: 99%
“…Although expression levels of annexins have been described as biomarkers for the prediction of disease severity 69 , our analysis using expiMap is the first to describe the expression of ligand–receptor pairs from the annexin pathway at the cellular level with the potential to interact between monocytes (CD14 + and CD16 + ), NK cells and T cells in COVID. The differences observed between patients in the expression of annexin-related interaction circuits may be related to the capability of viral clearance in each patient 62 and the early expression of FPR1 by CD16 + monocytes, which is associated with the early detection of pathogenic molecules and tissue damage 70 .…”
Section: Resultsmentioning
confidence: 99%
“…5f and Supplementary Fig. 11 ).Annexins are structural proteins that participate in multiple processes, including the regulation of inflammatory responses and homeostasis 61 ; recently, they have been associated with the disease severity of COVID-19 in patients requiring hospitalization 62,63 . In this circuit, CD14 + and CD16 + monocytes receive signals from NK cells and CD8 + T cells for P1D1, whereas for P1D5, the annexin circuit switches completely to signaling between CD16 + monocytes and CD4 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although expression levels of annexins have been described as biomarkers for the prediction of disease severity 63 , our analysis using expiMap is the first to describe the annexin circuit at the cellular level between monocytes (CD14 + and CD16 + ), NK cells, and T cells in COVID. The differences observed between patients in the expression of annexin-related interaction circuits may be related to the capability of viral clearance in each patient 56 and the early expression of FPR1 by CD16 + monocytes, which is associated with the early detection of pathogenic molecules and tissue damage 64 .…”
Section: Interpreting the Immune Response Of Patients With Covid-19 T...mentioning
confidence: 99%
“…Moreover, serum ANXA1 levels predicted a poor outcome 6 months after aSAH occurance [ 114] . Interestingly, a recent COVID‐19 study has shown that serum ANXA1 levels were significantly lower in samples from patients with severe disease compared to both healthy controls and those with moderate disease [ 115] . This suggests a potential role of ANXA1 as a biomarker in predicting COVID‐19 prognosis, which could allow for earlier treatment interventions.…”
Section: Anxa1 In Diseasementioning
confidence: 99%